The Korean Peninsula as a Hotbed of Cold War 2.0 - R. R. Kalinin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Contemporary international relations witness an ever-increasing tension between the United States and China. In an attempt to capture and conceptualize this trend, a new term was introduced in the IR academic discourse — a ‘Cold War 2.0’ (or new Cold War). Ambiguous and vague as it is, it may nevertheless be instrumental for the study of certain aspects of contemporary world politics. In particular, it allows one to consider the developments of the Korean Peninsula nuclear issue (KPNI) within the broader framework of emerging US-China confrontation. The first section examines current debates over the ‘Cold War 2.0’ concept both in Russian and foreign academic literature, and identifies its country-specific interpretations in the United States, Russia and the PRC. The second section shows that, despite its contested and controversial nature, the ‘Cold War 2.0’ concept provides useful insights on how concrete steps of global and regional actors aimed at enhancing their military capabilities are threatening to turn the Korean Peninsula into the arena of a new bipolar confrontation. In the third section, drawing on the Harvard negotiation model and the experience of 2005 Agreement, the author attempts to identify the zone of potential agreement on the KPNI under new conditions. The author concludes that both the leading powers and the countries of the Korean Peninsula utilize the ‘Cold War 2.0’ rhetoric to get additional domestic and foreign policy dividends. Thus, the DPRK relies upon the nuclear factor, while the Republic of Korea tries to balance between the great powers and to gain more weight in the international arena by building on the ‘medium power’ concept. In the long term, such policies are fraught with uncontrolled escalation that could lead to a new full-scale war on the Korean Peninsula.